Academician A.D. Makatsariya – Adjunct Professor of the University of Vienna - article Editorial (Акушерство, гинекология и репродукция)
Alexander Davidovich Makatsaria – obstetrician-gynecologist and world-renowned specialist in clinical hemostasiology, Professor, Doctor of Medical Sciences, Academician of the Russian Academy of Sciences, Vice-president of the Russian Society of Obstetricians and Gynecologists is an Adjunct Professor of the University of Vienna (Austria). In March 2022, the Rector's Office and the Academic Council of the Medical University of Vienna extended the powers of A.D. Makatsariya until 2025.